2001
DOI: 10.1034/j.1600-0420.2001.790304.x
|View full text |Cite
|
Sign up to set email alerts
|

An intervention trial on efficacy of atropine and multi‐focal glasses in controlling myopic progression

Abstract: ABSTRACT.Purpose: This randomized clinical trial assessed the treatment effects of atropine and/or multi-focal lenses in decreasing the progression rate of myopia in children. Methods: Two hundred and twenty-seven schoolchildren with myopia, aged from 6 to 13 years, who were stratified based on gender, age and the initial amount of myopia were randomly assigned to three treatment groups: 0.5% atropine with multi-focal glasses, multi-focal glasses, and single vision spectacles. Each subject was followed for at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
153
0
7

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(166 citation statements)
references
References 10 publications
(11 reference statements)
6
153
0
7
Order By: Relevance
“…Liu et al (54) demonstrated that muscarinic antagonists acted directly on the sclera to prevent myopia development induced by form deprivation in guinea pigs in which myopia progression was accompanied by overexpression of muscarinic acetylcholine receptors (M1 and M4). Furthermore, atropine, a nonselective muscarinic antagonist, and pirenzepine, an antagonist specific for M1, have been found to be effective in clinical trials to prevent myopia progression (55)(56)(57)(58). In experimentally induced myopia, including chicks and tree shrews, several muscarinic antagonists have been applied to control ocular growth in different species, although the mechanism of drug effects against myopia remain unclear (59 -61).…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al (54) demonstrated that muscarinic antagonists acted directly on the sclera to prevent myopia development induced by form deprivation in guinea pigs in which myopia progression was accompanied by overexpression of muscarinic acetylcholine receptors (M1 and M4). Furthermore, atropine, a nonselective muscarinic antagonist, and pirenzepine, an antagonist specific for M1, have been found to be effective in clinical trials to prevent myopia progression (55)(56)(57)(58). In experimentally induced myopia, including chicks and tree shrews, several muscarinic antagonists have been applied to control ocular growth in different species, although the mechanism of drug effects against myopia remain unclear (59 -61).…”
Section: Discussionmentioning
confidence: 99%
“…Although in most clinical studies atropine is used to treat 6-13-year-old children, [11][12][13][14][15] in Taiwan, 41.6% of 13-15-year-old children (junior high school students) and 28.5% of 16-18-year-old children (senior high school students) were still being prescribed atropine during 2007. The present study shows that atropine remains being prescribed to a certain portion of 13-18-year-old children, indicating that doctors are still concerned about myopia progression in these age groups.…”
Section: Discussionmentioning
confidence: 99%
“…Atropine has become part of routine eye care in Taiwan ever since the suggestion by the Taiwan Ophthalmology Association in the year 2000. Although evidences from many clinical trials on the use of atropine eye drops support a statistically significant reduction in myopia progression between experimental and control groups, [9][10][11][12][13][14][15][16] the clinical significance of the results of these trials are controversial. The routine use of atropine among children with myopia is not recommended in other countries.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies have shown some clinical effect on the progression of myopia in children. [68][69][70] In addition, atropine inhibits myopia in tree shrew and monkey myopia models and blocks form deprivation myopia or lens induced myopia in chicks. [71][72][73][74] In contrast to the mammalian eye, the avian eye contains striated intraocular muscle and atropine has neither mydriatic nor cycloplegic effect in birds, indicating a non accommodative mechanism for anti-myopia activity of atropine in chick.…”
Section: Medication Atropine Eyedropsmentioning
confidence: 99%